2018
DOI: 10.1182/blood-2018-05-852798
|View full text |Cite
|
Sign up to set email alerts
|

Crbn I391V is sufficient to confer in vivo sensitivity to thalidomide and its derivatives in mice

Abstract: Thalidomide and its derivatives, lenalidomide and pomalidomide, are clinically effective treatments for multiple myeloma and myelodysplastic syndrome with del(5q). These molecules lack activity in murine models, limiting investigation of their therapeutic activity or toxicity in vivo. Here, we report the development of a mouse model that is sensitive to thalidomide derivatives because of a single amino acid change in the direct target of thalidomide derivatives, cereblon (Crbn). In human cells, thalidomide and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 65 publications
4
77
0
Order By: Relevance
“…Sequence analysis reveals that mice and zebrafish have critical mutations in the ZnF2 domain of SALL4 ( Figure 5B ), which abrogate binding to hsCRBN in vitro ( Figure 4H ), and render mmSALL4 and drSALL4 insensitive to IMiD-mediated degradation in cells ( Figure 4G,I and Figure 4—figure supplement 1C ). In line with these findings, mice harboring a homozygous CRBN I391V knock-in allele, despite exhibiting degradation of mmIKZF1/3, mmZFP91, and mmCSNK1A1 Fink et al, 2018 , show increased miscarriage upon IMiD treatment compared with control mice; however, they do not exhibit IMiD-induced embryopathies resembling the human phenotype Fink et al, 2018 . We next sought to test whether exchange of the mmSALL4 ZnF2 domain for the hsSALL4 ZnF2 domain would be sufficient to enable mmSALL4 degradation in a human cell line (Kelly cells).…”
Section: Resultssupporting
confidence: 57%
“…Sequence analysis reveals that mice and zebrafish have critical mutations in the ZnF2 domain of SALL4 ( Figure 5B ), which abrogate binding to hsCRBN in vitro ( Figure 4H ), and render mmSALL4 and drSALL4 insensitive to IMiD-mediated degradation in cells ( Figure 4G,I and Figure 4—figure supplement 1C ). In line with these findings, mice harboring a homozygous CRBN I391V knock-in allele, despite exhibiting degradation of mmIKZF1/3, mmZFP91, and mmCSNK1A1 Fink et al, 2018 , show increased miscarriage upon IMiD treatment compared with control mice; however, they do not exhibit IMiD-induced embryopathies resembling the human phenotype Fink et al, 2018 . We next sought to test whether exchange of the mmSALL4 ZnF2 domain for the hsSALL4 ZnF2 domain would be sufficient to enable mmSALL4 degradation in a human cell line (Kelly cells).…”
Section: Resultssupporting
confidence: 57%
“…2), and in-solution TMT labeling-based methods. Because of these complexities and inefficiencies in using the SILAC quantification approach for ubiquitylation profiling in cells noted above, studies focused on identifying drug-induced substrates of E3 ubiquitin ligases are being carried out with increasing frequency by proteome profiling only rather than ubiquitin profiling 36,37 . The simplicity and speed of our on-antibody labeling approach opens the door to deep-scale ubiquitylation profiling to more directly identify the substrates of E3 ligases degraded by the proteasome degradation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A strength or weakness of the IKZF3 degron system, depending upon the application, is that mouse cereblon does not engage IKZF3 when bound to an IMiD. However, a mouse with a humanized cereblon has been developed (21). Two recent studies showed that indisulam redirects an ubiquitin ligase containing the substrate adaptor DCAF15 to degrade RBM39, much as the IMiDs redirect the cereblon ligase to target IKZF1 and IKZF3 for destruction (22,23).…”
Section: Discussionmentioning
confidence: 99%